2014
DOI: 10.1038/srep07233
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Chronic Bacterial Prostatitis on Semen Quality in Adult Men: A Meta-Analysis of Case-control Studies

Abstract: Chronic bacterial prostatitis (CBP) is caused by bacterial infection and maintains a condition of lower urinary tract infection. It may be a cause of male infertility. However, studies showed inconsistent results regarding the effect of CBP on several parameters of semen. Hence, we conducted a meta-analysis to examine the effect of CBP on basic semen parameters. A systematic review was conducted with Medline, PubMed, EMBASE, and two Chinese databases (CNKI and WANG FANG) to identify relevant studies that invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 37 publications
2
19
0
6
Order By: Relevance
“…All these symptoms are grouped in domains, termed UPOINTS [3,28] . With regard to semen quality, one controversial metaanalysis discussed the impact of chronic bacterial prostatitis on sperm vitality, sperm total motility, and the percentage of progressively motile sperm [6] . With regard to CP/ CPSS, there is accumulating evidence that CP/CPPS might negatively affect male fertility, although the mechanisms behind this are not understood [1,5,7] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All these symptoms are grouped in domains, termed UPOINTS [3,28] . With regard to semen quality, one controversial metaanalysis discussed the impact of chronic bacterial prostatitis on sperm vitality, sperm total motility, and the percentage of progressively motile sperm [6] . With regard to CP/ CPSS, there is accumulating evidence that CP/CPPS might negatively affect male fertility, although the mechanisms behind this are not understood [1,5,7] .…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis has shown that there was a significant negative effect of chronic bacterial prostatitis on sperm vitality, sperm total motility, and the percentage of progressively motile sperm [6] . The evidence in CP/CPPS is, however, less corroborated.…”
Section: Introductionmentioning
confidence: 99%
“…Вторым источником АФК в эякуляте являются лейкоциты, которые в физиологических условиях производят их до 1000 раз больше, чем сперматозоиды. Такой высокий уровень продукции АФК лейкоцитами играет важную роль в механизмах клеточной защиты от инфекций и воспаления, На утверждение однако увеличение количества лейкоцитов (лейкоцитоспермия) достоверно ассоциируется с ухудшением оплодотворяющей способности эякулята [63].…”
Section: ω-3-пнжк и мужское бесплодиеunclassified
“…Lifestyle habits, such as smoking, high BMI, and the increasing exposure to xenoestrogens, for example in drinking water, have been associated with reduced male fertility [4,5]. An additional hypothesis is that silent and/or chronic bacterial infections of the genital tract causing inflammation and direct deterioration of semen might partially explain some of the otherwise idiopathic cases [3,[6][7][8]. The well-known intracellular pathogen, Chlamydia trachomatis, which can cause urethritis and negatively impact spermatozoa physiology, may be a key example [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%